THE DIFFICULTIES OF FIFTH GRADE STUDENTS IN SOLVING MATHEMATIC FRACTIONS WORD PROBLEMS - May Nisa Istiqomah; Sufyani Prabawanto (Universitas Muhammadiyah Ponorogo, 2019)
Mathematics is often become the frightening subjects for students. Mathematics is considered as something which is difficult to solve. One of the elementary schools mathematics materials which is considered difficult is fractions. Not only students who consider fractions as difficult material but also teachers admit it as well. Teachers feel difficult in teaching fractions to students. Basic concept of fractions which is difficult for the student to grasp, would become even more complex if it is delivered in the form of word problem. In solving word problems students do not only need mathematic skills but also language skills. This research is aimed to analyze students learning difficulties in solving fractions word problem. This research is a qualitative research. The method of analysis used in this research is Newman method. The results of the research show that students faced difficulties in solving fractions word problems because (1) it is difficult for the students to understand the question and to translate it into mathematical sentence, (2) it is difficult for the students to determine the operation used in the word problems, (3) students are not accustomed to, thus they forget to write the conclusion/write the conclusion without the unit in every answers.